Applications of multivariate data analysis in shelf life studies of edible vegetal oils – A review of the few past years - Martín-Torres, Sandra; Ruiz-Castro, Laura; Jiménez-Carvelo, Ana M.; Cuadros-Rodríguez, Luis (Food packaging and shelf life, 2022)
The physical-chemical and organoleptic properties of vegetal oils are subject to frequent change caused by different degradation process. Hence, producers must provide accurate information on shelf-life prediction. Due to the complexity of chemical interactions between the oil phase and environment, multiple studies under real-time storage and forced conditions have been conducted. This paper reviews the application of methods based on multivariate data analysis, and its advantages, in shelf life and stability studies of edible both virgin and refined vegetable oils. Three multivariate approaches could mainly be differentiated regarding previous studies on foodstuff stability data: unsupervised methods; multivariate pattern recognition methods; and other chemometric resolution methods. Note that, multivariate approaches bring numerous opportunities, these applications currently show also limitations, especially for official control purposes in food surveillance. Future trends will rely on the practical implementation of such promising chemometric approaches combining high informative advanced techniques and comprehensive multivariate data analysis. •Dietary lipid oxidation is a major cause of food quality deterioration.•Wide number of parameters can be monitored to assess the stability of oils.•Univariate stability models are extremely condition dependent.•Detailed review of multivariate approaches on oil stability and shelf life studies.